Flexible quasi-solid-state sodium-ion capacitors developed using 2D metal-organic-framework array as reactor - Xu, Dongming (2019)
Achieving high-performance Na-ion capacitors (NICs) has the particular challenge of matching both capacity and kinetics between the anode and cathode. Here we report a high-power NIC full device constructed from 2D metal-organic frameworks (MOFs) array as the reactive template. The MOF array is converted to N-doped mesoporous carbon nanosheets (mp-CNSs), which are then uniformly encapsulated with VO2 and Na3V2(PO4)3 (NVP) nanoparticles as the electroactive materials. By this method, we are able to enhance significantly the high-power performance of the battery materials. It is discovered that such hybrid NVP@mp-CNSs array can render ultrahigh rate capability (up to 200 C, equivalent to discharge within 18 s) and superior cycle performance, which outperforms all NVP-based Na-ion battery cathode reported so far. We further assemble a quasi-solid-state flexible NIC based on the NVP@mp-CNSs cathode and the VO2@mp-CNSs anode. This hybrid NIC device delivers both high energy density and power density as well as a good cycle stability (78% retention after 2000 cycles at 1 A g−1 ). Our results demonstrate the powerfulness of MOF array as the reactor for fabricating electrode materials.